A Comparison of Outflow Properties in AGN Dwarfs versus Star-forming Dwarfs - Archana Aravindan; Weizhe Liu; Gabriela Canalizo; Sylvain Veilleux; Thomas Bohn; Remington O. Sexton; David S. N. Rupke; Vivian U (The Astrophysical Journal, 2023)
Feedback likely plays a crucial role in resolving discrepancies between observations and theoretical predictions of dwarf galaxy properties. Stellar feedback was once believed to be sufficient to explain these discrepancies, but it has thus far failed to fully reconcile theory and observations. The recent discovery of energetic galaxy-wide outflows in dwarf galaxies hosting active galactic nuclei (AGNs) suggests that AGN feedback may have a larger role in the evolution of dwarf galaxies than previously suspected. In order to assess the relative importance of stellar versus AGN feedback in these galaxies, we perform a detailed Keck/KCWI optical integral field spectroscopic study of a sample of low-redshift star-forming (SF) dwarf galaxies that show outflows in ionized gas in their Sloan Digital Sky Survey spectra. We characterize the outflows and compare them to observations of AGN-driven outflows in dwarfs. We find that SF dwarfs have outflow components that have comparable widths ( W _80 ) to those of outflows in AGN dwarfs, but are much less blueshifted, indicating that SF dwarfs have significantly slower outflows than their AGN counterparts. Outflows in SF dwarfs are spatially resolved and significantly more extended than those in AGN dwarfs. The mass-loss, momentum, and energy rates of star-formation-driven outflows are much lower than those of AGN-driven outflows. Our results indicate that AGN feedback in the form of gas outflows may play an important role in dwarf galaxies and should be considered along with SF feedback in models of dwarf galaxy evolution.